TMPRSS2 Serves as a Prognostic Biomarker and Correlated With Immune Infiltrates in Breast Invasive Cancer and Lung Adenocarcinoma - Xiao, Xinhua; Shan, Huizhuang; Niu, Yangyang; Wang, Peihong; Li, Donghe; Zhang, Yuyin; Wang, Jiayi; Wu, Yingli; Jiang, Hua (Frontiers in Molecular Biosciences, 2022)
TMPRSS2 is a transmembrane serine protease and has a pivotal role in coronavirus disease 2019 (COVID-19). However, the correlation of TMPRSS2 with prognosis and tumor immune infiltration in tumor has not yet been explored. Here, we analyzed the expression of TMPRSS2 in Oncomine and TIMER databases, the correlation between TMPRSS2 and overall survival in the PrognoScan, Kaplan-Meier plotter and GEPIA databases. The association between TMPRSS2 and immune infiltration levels was investigated in TIMER database. In addition, the prognosis of TMPRSS2 related to immune cells in cancers was analyzed. Real-time PCR confirmed that TMPRSS2 was upregulated in lung adenocarcinoma (LUAD) and downregulated in breast invasive carcinoma (BRCA). We found that high TMPRSS2 expression was associated with favorable prognosis in LUAD, whereas, high TMPRSS2 expression was associated with poor prognosis in BRCA. Interestingly, we found that TMPRSS2 expression levels was significantly correlated with immune infiltration of B cells, CD4+ T cells, macrophages and dendritic cells in LUAD, and TMPRSS2 expression was positively correlated with the infiltrating levels of CD8+ T cells, CD4+ T cells, neutrophils and dendric cells in BRCA. Consistent with the prognosis of TMPRSS2 in LUAD and BRCA, high expression level of TMPRSS2 has a favorable prognosis in enriched immune cells such as B cells, macrophages and CD4+ T cells in LUAD, TMPRSS2 expression level has a poor prognosis in CD4+ T cells and CD8+ T cells in BRCA. In conclusion, we found that the prognosis of TMPRSS2 in LUAD and BRCA is significantly correlated with immune cells infiltration. Our study comprehensively revealed the relationship between the prognosis of TMPRSS2 in pan-cancers and tumor immune. Keywords: TMPRSS2, tumor immune infiltrating cells, prognosis, breast invasive cancer, lung adenocarcinoma